Bose-Einstein condensation for general dispersion relations - Aguilera-Navarro, V. C. [UNESP]; De Llano, M.; Solís, M. A. (IOP Publishing, 1999)
Bose-Einstein condensation in an ideal (i.e. interactionless) boson gas can be studied analytically, at university-level statistical and solid state physics, in any positive dimensionality (d > 0) for identical bosons with any positive-exponent (s > 0) energy-momentum (i.e. dispersion) relation. Explicit formulae with arbitrary dls are discussed for: the critical temperature (non-zero only if d/s > 1); the condensate fraction; the internal energy; and the constant-volume specific heat (found to possess a jump discontinuity only if d/s > 2) Classical results are recovered at sufficiently high temperatures. Applications to ordinary' Bose-Einstein condensation, as well as to photons, phonons, ferro-and antiferromagnetic magnons, and (very specially) to Cooper pairs in superconductivity, are mentioned.